Specific Detection of Fasciola hepatica and F. gigantica in Infected Domesticated Animals Using High-Resolution Melting Analysis (HRM) - Zeinab MOGHADAMIZAD; Ahmad HOSSEINI-SAFA; Mehdi MOHEBALI; Peyman HEYDARIAN; Mojgan ARYAEIPOUR; Mohammad Bagher ROKNI (Tehran University of Medical Sciences, 2020)
Background: It is difficult to make an exact morphological distinction between Fasciola hepatica and Fasciola gigantica. We used High Resolution Melting analysis (HRM) method to differentiate the F. hepatica species from F. gigantica in order to differentiate them. Methods: Overall, 80 adult liver flukes were collected from infected slaughtered animals including cattle, sheep and goats from Lorestan Province, western Iran from Sep 2015 to Aug 2017. Genomic DNA was extracted using commercial DNA extraction kit. The multilocus sequences of mDNA including COX1, COX3 and ND6 were amplified employing real-time PCR & HRM analysis. Specific and universal primer pairs were designed for differentiation Fasciola spp. Results: Universal primers cannot be used to distinguish between these two species, but in the contrary, specific primer pairs of each species could differentiate them properly. Molecular identification using specific primer pairs were consistent. Conclusion: HRM is a simple, fast and reliable method for detecting and differentiating F. hepatica from F. gigantica and can be used for diagnostic and epidemiological purposes.